2021
DOI: 10.1101/2021.10.27.466071
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spindle - slow oscillation coupling correlates with memory performance and connectivity changes in a hippocampal network after sleep

Abstract: After experiences are encoded, post-encoding reactivations during sleep have been proposed to mediate long-term memory consolidation. Spindle-slow oscillation coupling during NREM sleep is a candidate mechanism through which a hippocampal-cortical dialogue may strengthen a newly formed memory engram. Here, we investigated the role of fast spindle- and slow spindle-slow oscillation coupling in the consolidation of spatial memory in humans with a virtual water maze task involving allocentric and egocentric learn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 79 publications
(123 reference statements)
1
1
0
Order By: Relevance
“…Importantly, accumulating findings support the conjecture that primarily canonical fast SPs coalesce with the up peak of SOs, while slow SPs are synchronized more towards the down peak (Bastian et al, 2022; Kurz et al, 2021; Mölle et al, 2011; Muehlroth et al, 2019). If merely the absolute frequency range of SPs would determine the coupling pattern, one might have simply expected to find a phase shift in coupling with older age and accompanying faster SPs.…”
Section: Discussionsupporting
confidence: 62%
“…Importantly, accumulating findings support the conjecture that primarily canonical fast SPs coalesce with the up peak of SOs, while slow SPs are synchronized more towards the down peak (Bastian et al, 2022; Kurz et al, 2021; Mölle et al, 2011; Muehlroth et al, 2019). If merely the absolute frequency range of SPs would determine the coupling pattern, one might have simply expected to find a phase shift in coupling with older age and accompanying faster SPs.…”
Section: Discussionsupporting
confidence: 62%
“…Although we were able to investigate a large sample of baseline sleep recordings, we were limited to a single frontal EEG derivation, and there were no behavioral tasks available to associate memory, executive functions or other cognitive domains to SW-spindle coupling. However, among other studies that did measure memory, there is a strong consensus that a "younger" SW-spindle coupling physiology is optimal for memory consolidation, and age-related changes in coupling are associated with reduced memory performance (Bastian et al, 2022;Chylinski et al, 2022;Helfrich et al, 2018;Ladenbauer et al, 2017;Mikutta et al, 2019;Muehlroth et al, 2019).…”
Section: Limitationsmentioning
confidence: 99%
“…For optimal functionality, the layers of this hierarchy are organized in a relationship of phase-amplitude coupling, where the faster spindles are nested into the depolarizing up-phase of the slower SW. This allows for synchronized, widespread communication during periods of high responsiveness and therefore efficient top-down control of processes like memory consolidation (Bastian et al, 2022;Helfrich et al, 2018;Mikutta et al, 2019;Rasch & Born, 2013;Tort et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Connectivity in the DMN varies in accordance with sleep patterns. In the healthy brain, connectivity has been observed to decrease during short wave sleep, possibly to aid in the consolidation and long-term storage of memories [166]. Positron emission tomography (PET) studies have shown that DMN connectivity is heightened during poor sleep, and, in AD and MCI subjects, it is in this poor sleep state that Aβ deposition is upregulated [158].…”
Section: Connections Between Ad and Circadian Dysfunctionmentioning
confidence: 99%